CASE REPORT OF SYNOVIAL SARCOMA PRESENTING AS A THIGH SWELLING - KUMAR, BINAY; PRASAD, NIDHI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Synovial sarcoma (SS) is a rare tumor arising from the mesenchymal lining and commonly arising near proximity of joint. The tumor is difficult to diagnose initially or can be misdiagnosed due to its site and slow-growing potential. This is a malignant tumor with genetic predisposition and has a poor prognosis, if metastasizes to distant organs. The current study tries to describe the clinical, histopathological and immunochemistry findings of synovial sarcoma. A case of SSs presented in our institute for surgery and histopathological examination. Relevant history was taken retrospectively and consent of the patient was also taken. The treatment modality consists of wide excision surgery, chemotherapy, and radiotherapy. In this case, a 35 years old having tumor growth involving thigh area, the excised tumor was sent to our department for histopathological examination. On HPE, monophasic spindle cell tumor was diagnosed with differential diagnosis of SS or malignant peripheral nerve sheath tumor and immunohistochemistry staining was done for further confirmation.